Growth of Companies and Growth Potential on the Example of Business Services for Firms Sector on NewConnect Market - Bolek, Monika; Czulak, Bartosz (Journal of Finance and Financial Law, 2020)
The article is related to the growth of young companies operating in the business services for firms sector, that are listed on the Warsaw Stock Exchange alternative market – NewConnect. The growth opportunity models are introduced to explain the growth process of these companies together with other controlling factors such as profitability, size of the company and its earnings. As the result of the research it is found that growth potential is negatively correlated with assets and equity growth in short term, but it affects positively earnings per share growth in a longer, three-year period. It can therefore be concluded that in the sector taken into consideration, investors’ decisions reflected in the growth potential measures may be translated into company’s value growth only in a longer term.